LA FRECUENCIA DEL TIFO EN GUADALAJARA - RUIZ SANCHEZ; PONCE DE LEON; OROZCO GARCIA (Instituto Nacional Nutriologico, CD MEXICO, DF, MEX, 1946)
The centrosomes and centrioles of the ependyma in malignant tumors show atypical variations; the greater the malignancy, the greater the abnormality The centrioles may be found in varying numbers in the centrosomes, or they may be found free in the proto
REV MEX MED
Keywords: FRECUENCIA, TIFO, GUADALAJARA; CIENCIAS MEDICAS; SALUD PUBLICA